(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
Moral arguments pertaining to commercial surrogate pregnancy have been framed as questions on the appropriate scope of markets. Should pregnancies be conceived and regulated as services that can be exchanged in markets? It has been argued that surrogacy is an exceptional form of labour, and hence inappropriately commodified, because of its nature. Commercial surrogacy involves the bodies and identities of women in a most invasive manner, it negatively affects motherhood and it inappropriately treats babies and surrogates as commodities. We find these arguments wanting: the nature of gestational surrogacy does not make it an exceptional form of labour, and indeed the commodification of pregnancy may disrupt oppressive conceptions of human reproduction. We argue instead that surrogacy does raise major moral concerns insofar as it may exacerbate extant patterns of domination and exploitation based on international inequities and gender-based discrimination. However, the moral problems of surrogacy extend to wage labour more generally. In other words, surrogate pregnancy is not an exceptional form of labour, but human labour is an exceptional commodity.